A review of the genus Ephysteris Meyrick, 1908 from China, with descriptions of two new species (Lepidoptera: Gelechiidae) - Li, Houhun; Bidzilya, Oleksiy (Zootaxa, 2008)
Six Chinese species of the genus Ephysteris Meyrick are reviewed. Ephysteris montana sp. nov. is described from Sichuan and E. wenquana sp. nov. is described from Yunnan. Hitherto unknown male of E. subovata Povolný, 2001 and unknown female of E. flavida Povolný, 1969 are described. Descriptions and a key for all species are provided, with illustration of the adults, male and female genitalia.